The effect of microalgae biodiesel on combustion, performance and emission characteristics of a diesel power generator - Yasar Fevzi (Thermal Science, 2018)
Microalgae oil is expected to be a relevant source of biofuel in the future as it is more favorable to confront the problems of food shortages and greenhouse emission challenges raised by conventional biofuels. Therefore, in this study, a most common kind of microalgae that have a great potential, Chlorella protothecoides, was evaluated as fuel in terms of its combustion and emission characteristics in a Diesel engine-powered generator set at constant engine speed of 1500 rpm under various loads after converting its oil to biodiesel by typical base-catalyzed transesterification process. A biodiesel/diesel blend at the rate of 20% by volume was tested too. According to results obtained, using biodiesel resulted in an increase in fuel consumption, in a slight reduction of efficiency, and in sharp reductions in both unburned hydrocarbon emissions and smoke opacity especially at light loads, despite increasing NOx emissions were observed when compared with conventional petroleum diesel. In addition, premixed combustion ratio was higher for biodiesel than for diesel while total combustion duration took shorter for biodiesel especially at higher loads. The overall results of the study reveals that the combustion parameters of the biodiesel studied here are within the typical ranges of conventional biodiesel fuels.